TEKNIK COPRAS UNTUK EVALUASI KEPUASAN SISWA TERHADAP KINERJA GURU DI MAS ALWASHLIYAH PETATAL - Lestari, Eva; Rahmadani, Nurul; Lubis, Iin Almeina (J-Com (Journal of Computer), 2025)
Abstract: Student satisfaction with teacher performance plays a crucial role in improving the quality of education. Teacher performance evaluation is necessary to understand how well teaching meets student expectations. This study evaluates student satisfaction with teacher performance at MAS Alwashliyah Petatal using the COmplex PRoportional ASsessment (COPRAS) method, which effectively handles multi-criteria comparisons objectively. Data were collected through questionnaires completed by 66 out of 209 students (31.58% response rate), assessing 16 teachers based on four competency aspects: pedagogical, personality, social, and professional, with 12 sub-criteria. Despite the low participation rate, the data remained representative based on response distribution analysis. The results indicate that the COPRAS method accurately ranks teacher performance, with teacher Lia Novia, S.Pd achieving the highest satisfaction score (100%). These findings can be integrated into school policies, such as annual teacher evaluations and teacher development programs. The implementation of this evaluation system can also serve as a basis for designing teacher training that better aligns with student needs. Thus, the COPRAS method not only helps schools assess teacher performance more objectively but also supports more effective decision-making to enhance teaching quality and overall student satisfaction.            Keywords: COPRAS; evaluation; decision support system, student satisfaction; teacher performance Abstrak: Kepuasan siswa terhadap kinerja guru berperan penting dalam meningkatkan kualitas pendidikan. Evaluasi kinerja guru diperlukan untuk memahami sejauh mana pengajaran memenuhi harapan siswa. Penelitian ini mengevaluasi tingkat kepuasan siswa terhadap kinerja guru di MAS Alwashliyah Petatal menggunakan metode COmplex PRoportional ASsessment (COPRAS), yang mampu menangani perbandingan multi-kriteria secara objektif. Data diperoleh dari kuesioner yang diisi oleh 66 dari 209 siswa (tingkat respons 31,58%), menilai 16 guru berdasarkan empat aspek kompetensi, yaitu pedagogik, kepribadian, sosial, dan profesional, dengan 12 sub-kriteria. Meskipun partisipasi rendah, data tetap representatif berdasarkan analisis distribusi jawaban. Hasil penelitian menunjukkan bahwa metode COPRAS memberikan pemeringkatan kinerja guru secara akurat, di mana guru Lia Novia, S.Pd memperoleh nilai kepuasan tertinggi (100%). Hasil ini dapat diintegrasikan dalam kebijakan sekolah, seperti evaluasi tahunan guru dan program pengembangan tenaga pendidik. Implementasi sistem evaluasi ini juga dapat digunakan sebagai dasar penyusunan pelatihan guru yang lebih sesuai dengan kebutuhan siswa. Dengan demikian, metode COPRAS tidak hanya membantu sekolah dalam menilai kinerja guru secara lebih objektif tetapi juga mendukung pengambilan keputusan yang lebih tepat untuk meningkatkan mutu pengajaran dan kepuasan siswa.Kata kunci: COPRAS; evaluasi; kepuasan siswa; kinerja guru; sistem pendukung keputusan